Vulnerability Map for Response to the COVID-19 Epidemic : A Case Study on Indonesia - Hou, Xiaohui (Washington, DC: World Bank, 2022)
The COVID-19 pandemic has emerged as a threat to global health security. This paper uses geospatial analyses to create a COVID Vulnerability Mapping Dashboard that examines and displays social vulnerability indices at the national and subnational levels in Indonesia. The dashboard answers three main questions: 1. Where are the vulnerable populations 2. What is the capacity of local health systems and 3. What is the local trend in COVID cases The dashboard prototype presented herein was developed and used to direct attention to geographic areas where risks are expected to be greatest.